Speech encryption by multiple chaotic map with fast fourier transform - Yahia Alemami; Mohamad Afendee Mohamed; Saleh Atiewi; Mustafa Mamat (International Journal of Electrical and Computer Engineering (IJECE), 2020)
There are various ways of social communication including writing (WhatsApp, Messenger, Facebook, Twitter, Skype, etc), calling (mobile phone) and voice recording (record your voice and then send it to the other party), but there are ways to eavesdropping the calls and voice messages, One way to solve this problem is via cryptographic approach. Chaos cryptography build on top of nonlinear dynamics chaotic system has gained some footstep in data security. It provides an alternative to conventional cryptography built on top of mathematical structures. This research focuses on the protection of speech recording by encrypting it with multiple encryption algorithms, including chaotic maps (Logistic Map and Sine Maps).